THE HISTORICAL INFLUENCE OF EDUCATIONAL THOUGHT ON THE DEVELOPMENT OF PHYSICAL EDUCATION IN SCHOOLS - Mohamed Ahmed Hassan (Proximus Journal Publishing, 2025)
This study aims to analyze the dialectical relationship between educational thought and the development of physical education in schools from a historical and comparative philosophical perspective. The research adopts a historical-analytical methodology supported by critical literature in educational philosophy and addresses how the content of physical education has been shaped by shifts in societal values and educational systems. The findings reveal that physical education has never been neutral or autonomous but has consistently mirrored dominant ideologies ranging from the idealism of Plato and Aristotle to Rousseau’s natural freedom then Dewey’s pragmatism and finally the emancipatory visions of Freire. The study highlights the transformation of physical education from a tool of discipline and control into a means of empowerment and self-expression especially within contemporary democratic and pluralistic contexts. It recommends reframing physical education within the modern educational curriculum as a fundamental domain for shaping the holistic human being in body thought and values in alignment with the demands of social justice and inclusive education
Keywords: educational thought; physical education body; school philosophical